Komunikasi Terapeutik dan Kecemasan Pasien Rawat Inap Bedah : Tinjauan Pustaka - Lazdia, Wenny; Cahyani, Atika Afri; Kartika, Imelda Rahmayunia (Universitas Fort De Kock Bukittinggi, 2021)
Background: Anxiety is something not clear. Anxiety or uneasy is not specific and unknown to someone. In order to reduce anxiety in preoperative patients, an effective communication should be done, especially therapeutic communication. It needs serious attention from nurses because nurses are the closest and longest-standing health workers to patients. The effect of providing information about surgery preparation with a therapeutic communication approach on patients anxiety levels. One of the efforts that can reduce the level of patient anxiety is the therapeutic communication of nurses. Methods: The design was of this reasech was literature review. Articles were collected by using Google Scholar and Google from publication in 2010-2020. Result: Based on the articles collected, the results found that that therapeutic communication can reduce patient anxiety. Nurses can apply therapeutic communication as an independent intervention as an effort to reduce patient anxiety.Keywords: Therapeutic Communication, Anxiety